1999
DOI: 10.1017/s0007114599000094
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise affects the lipid profile of mitochondrial membranes in rats fed with virgin olive oil or sunflower oil

Abstract: The effects of physical exercise on the lipid profile in mitochondrial membranes of liver and skeletal muscle were examined in rats fed with virgin olive oil or sunflower oil. Thirty male Wistar rats, 21 d old, were randomly assigned to four groups according to fat ingestion and physical activity over an 8-week period. For each type of oil, one group acted as a control group while rats from the other were trained to run for 40 min daily on a horizontal treadmill, at a speed of 35 m/min. The results show that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 11 publications
4
37
0
4
Order By: Relevance
“…Concerning the liver, a number of studies have examined the effect of exercise training on the fatty acid profile of total lipids in either the whole tissue (Fiebig et al 1998(Fiebig et al , 2002Wirth et al 1980) or subcellular fractions such as mitochondria (Mataix et al 1998;Quiles et al 1999) and microsomes (Venkatraman et al 1998a, b). Only Sˇimko et al (1970) have reported data on individual lipid classes, in particular triacylglycerols (TG) and cholesteryl esters of the whole tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the liver, a number of studies have examined the effect of exercise training on the fatty acid profile of total lipids in either the whole tissue (Fiebig et al 1998(Fiebig et al , 2002Wirth et al 1980) or subcellular fractions such as mitochondria (Mataix et al 1998;Quiles et al 1999) and microsomes (Venkatraman et al 1998a, b). Only Sˇimko et al (1970) have reported data on individual lipid classes, in particular triacylglycerols (TG) and cholesteryl esters of the whole tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a number of researchers have analyzed total lipids in subcellular fractions of muscle tissue, i.e., mitochondria (Mataix et al 1998;Quiles et al 1999Quiles et al , 2001 and membranes (Thomas et al 1977) before and after exercise training. However, there appears to be no consensus as to the effect of exercise.…”
Section: Introductionmentioning
confidence: 99%
“…The type of dietary fat influences several biochemical parameters at the mitochondrial membrane level [7,8]. The importance of fatty acids resides in the fact that the mitochondrial membrane (as do other biological membranes) adapts its lipid composition to some extent in response to dietary fat [9][10][11].…”
Section: Dietary Fat Type and Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…Oxidative stress is involved in the action of doxorubicin, in terms of both antitumour effects and cardiotoxicity [20]. Thus, it has been reported that doxorubicin leads to direct oxidative injury to DNA [21] and generates lipid peroxidation [8,9,13,15,22,23]. In relation to the cardiotoxicity of doxorubicin, the heart is very sensitive to free radical damage because it has a high rate of oxidative metabolism and a lower level of antioxidant defences than other organs, such as the liver.…”
Section: Olive Oil In the Prevention Of Doxorubicin-mediated Oxidativmentioning
confidence: 99%
See 1 more Smart Citation